2002
DOI: 10.1159/000063782
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenases in the Collecting Duct of Neonatal Rabbit Kidney

Abstract: COX 1 and 2 expression during the terminal phase of kidney development is poorly understood. To obtain information about this process we followed the primary appearance of cyclooxygenases in collecting duct (CD) epithelia of the neonatal rabbit kidney with immunohistochemical and two dimensional electrophoretical methods. In the fully embryonic cortical zone immunohistochemical expression of COX 1 is seen in all cells of the CD ampulla, while COX 2 is lacking within the nephron inducer. Within the matured cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In the adult kidney cortex, constitutive expression of COX2 is found mainly in the thick ascending limb of the loop of Henle (28), which is one of the main sites of water reabsorption. Schumacher et al (29) recently demonstrated on cryosections of neonatal rabbit kidneys that both COX1 and COX2 are constitutively expressed in the medullary collecting duct, without labeling the cortical collecting duct. This suggests a direct role of COX2 inhibition in the medullary collecting duct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the adult kidney cortex, constitutive expression of COX2 is found mainly in the thick ascending limb of the loop of Henle (28), which is one of the main sites of water reabsorption. Schumacher et al (29) recently demonstrated on cryosections of neonatal rabbit kidneys that both COX1 and COX2 are constitutively expressed in the medullary collecting duct, without labeling the cortical collecting duct. This suggests a direct role of COX2 inhibition in the medullary collecting duct.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies do not allow us to conclude definitely on the selectivity of nimesulide in our model. We therefore cannot totally exclude the possibility that the reduction of CH 2 O by nimesulide might also result from partial COX1 inhibition, as COX1 is widely expressed in the collecting duct (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also previously demonstrated in the same model that the newborn's kidney is highly sensitive to cyclooxygenase 2 (COX2) inhibition and that PGs play a key role in the regulation of neonatal GFR [29], through a rapid increase of COX2 renal expression during the first two postnatal weeks [38,39]. Prostaglandin synthesis inhibition with indomethacin completely blocked the IGF-1-induced increase in GFR in vitro and in vivo [24,40,41].…”
Section: Discussionmentioning
confidence: 77%
“…As a consequence, for special demands culture media have to be adapted by addition of defined electrolyte concentrations so that an adequate degree of differentiation is achieved (Schumacher et al , 2002b.…”
Section: Featuring Development Of Epitheliamentioning
confidence: 99%